(untitled) (Fiep Bulletin - online, 2011)
The health care practice in indigenous health carries the health staff to a very different reality. It is unlike that reality of professional and personal education, mainly when the issues are cultural diversity, ethnicity and specific legislation. A set of law that guide the indigenous questions and need be shaped to health care delivered to these populations. This article intends identify, synthesize and analyze the contextual aspects of indigenous healthcare in Brazil in 2008 and 2009. This article is a report of an integrative review about the indigenous health in Brazil. Searches were made in electronic database of the SCIELO and LILACS using the terms ’indigenous health’. The contextual analysis divided in four nested contextual layers (immediate, specific, general, and meta contexts) was used as theoretical reference. Nine articles were included and were analyzed in accordance to the theoretical reference. Results revealed that the life conditions and health of indigenous people are still in disadvantage. It makes the health staff work in an immediate context to attend the specific needs of the population. Despite having an ideal policy and resource available, the indigenous healthcare bumps up in management problems and lack of a transversal policy.